Factors Related to Post-traumatic Stress Disorder Symptoms Among Intensive Care Unit Nurses - SuHee Kim; YeoJin Im (Elsevier, 2024)
s u m m a r y: Purpose: The aim of this study was to identify the factors affecting the post-traumatic stress disorder (PTSD) symptoms of intensive care unit (ICU) nurses. The variables include event experiences, cognitive flexibility, and co-worker support. Methods: A survey was conducted among 153 ICU nurses working in a general hospital or an advanced general hospital. The questionnaire was completed between October and December 2018, and 153 copies were used for the final analysis. Data were analyzed using multiple linear regression to determine the factors associated with PTSD symptoms among ICU nurses. Results: The level of PTSD symptoms of ICU nurses was 1.20 ± 0.82 out of 4. Full PTSD, signified by a total score of 25 or more, was reported by 45.1% of the study's 153 participants. The significant influencing factors of PTSD symptoms among ICU nurses were the "experience of traumatic events," "trusted alliance," which is a subarea of "coworker support," and both "control" and "alternative," which are subareas of "cognitive flexibility." The explanatory power (49.8%) was statistically significant. Conclusions: These results suggest that a program to enhance the cognitive flexibility and coworker support of ICU nurses needs to be developed to reduce the PTSD symptoms of ICU nurses.